"MAKING REASON THINK MORE": laughter in kant's aesthetic philosophy. Issue 4 (2nd October 2017) - Giamario, Patrick T.
Abstract: This article explores the surprisingly decisive role that Kant's "incongruity theory" of laughter plays in his aesthetic and broader critical philosophy. First, laughter constitutes a highly specific form of aesthetic judgment in Kant. Laughter involves a discordant relation between the cognitive faculties characteristic of the sublime, but this relation obtains between the understanding and the imagination, the two faculties at play in judgments of taste on the beautiful. Second, laughter is the transcendental condition of possibility for both the beautiful and the sublime. While most commentators dismiss laughter as an afterthought of Kant's aesthetics, laughter in fact constitutes the most basic aesthetic judgment in Kant. Third, an account of aesthetic judgment that begins with laughter transforms how we understand Kant's argument that judgment unites nature and freedom. Namely, it reveals how an empirical world at odds with the subject's purposes can nevertheless advance the subject's rational vocation to think and act beyond the empirical. I conclude by arguing that Kantian critical philosophy is itself a philosophy of laughter.